Preparation and characterization of fluff from bamboo as source of fibre for the production of hygiene products - Gunjan Dhiman; Arvind Sharma; Deepak Sharma; Priti S. Lal (Advances in Bamboo Science, 2025)
This work explores the utilization of the bamboo Dendrocalamus strictus in place of softwood for the production of fluff. Unbleached kraft bamboo pulp was prepared using Kraft pulping. Pulping was done by applying 19 % chemical charge (as Na2O) to get the desired kappa number (14.5) of unbleached pulp. The unbleached bamboo pulp was bleached through ECF (Elemental Chlorine Free) and TCF (Total Chlorine Free) bleaching sequences to assess the impact of bleaching chemicals on fluff properties. A Sprout Waldron lab disc refiner was used to hammer the bleached bamboo pulp into fluff. FE-SEM images clearly showed the difference in fibre morphology before and after hammering. The bamboo fluff was analyzed for various parameters and compared to softwood fluff. The results established the suitability of bamboo as a source of fibre for the production of fluff. Morphological characteristics of bamboo and softwood before and after refining were compared to check the impact on fibre properties. After hammering, the pulp fibre was shortened. ECF bleached pulp demanded more energy than TCF bleached pulp during hammering. The physical strength properties of both bamboo ECF fluff and bamboo TCF fluff pads were also determined and compared with softwood fluff.